Students’ Perception Of The Use Of Quizizz Paper Mode On Reading Skills - Ziyadatul Mukarromah; Nurul Afidah; Luluk Choirun Nisak Nur; Yuyun Bahtiar (SCHOOLAR: Social and Literature Study in Education, 2026)
This study aims to determine students' perceptions of the use of Quizizz Papermode in reading skills at Islamic Junior High School Khozinatul Ulum Gunungrejo Lamongan, and to identify obstacles that arise during its implementation. This study uses the Mixed Method Concurrent design, with qualitative data as the main source obtained through observation, interviews, and documentation, and quantitative data from questionnaires. The results showed that students had a very positive perception of the use of Quizizz Papermode. This medium was considered interesting, enjoyable, easy to use, and able to increase students' motivation and understanding in analyzing parts of sentences in reading texts. The obstacles found were minor, namely the adaptation process in the first meeting and technical constraints in the form of projector damage. However, these obstacles did not interfere with the learning process. The questionnaire results, with an average index of 88.9%, reinforce that students did not experience significant difficulties during the use of Quizizz Papermode. Overall, Quizizz Papermode proved to be effective and practical as an evaluation medium that can increase student engagement and reading skills, especially in schools with limited digital facilities.